(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: The escape in the classes of Physical education in the Medium Teaching has been a frequent problem for the teachers and managers of the schools. OBJECTIVE: To analyze critical aspects of the escape in the classes of Physical education and of the intervention in the medium teaching. METHODOLOGY: He/she elapses of a study traverse, descriptive, random probabilístico, of field with a sample of 100 students of the 3° year of the Medium Teaching, morning shift, of E.E.M. Governor Adauto Bezerra, Juazeiro of the North, Ceará, submitted to the questionnaire elaborated by the researcher and guiding, for the collection of data in the school atmosphere, during the year of 2003. The analytical plan used the computerized statistical package SPSS version 13.0 for calculations of percentile of frequency. Level of trust 5%. The found RESULTS were: 80% don’t participate in the classes of Physical education, inside of these, 73% attribute to the work, the main reason of they miss the classes; 93% find the necessary discipline for the curriculum; 87% answered that you/they would like to practice more sports, 9% gymnastics and 4% games; 93% of the students attribute to the discipline a great value and the presented suggestions, they were: 70% would like the classes to happen in the normal schedule of class. CONCLUSIONS: The main reason of the escape in the classes of Physical education is the factor work, due to the normal schedules of class, they beat not with the schedule of the classes of Physical education. If the nucleus manager got to insert the classes of Physical education in the normal schedule of classes, this escape would reduce.